The profitability of formation for employment in Colombia - Uribe García, José Ignacio; Universidad del Valle (Pontificia Universidad Javeriana, 2011)
This work studies formation for employment in the Colombian labour market, based on the quality of life survey made in 2003 by the statistical bureau DANE. It uses Mincerian functions to find that the profitability of formation for employment among workers increases with the level of formal education; it also finds that employment income increases with the size of the company. The descriptive analysis allows it to be concluded that corporate investment in formation for employment increases with size. These results suggest that there is a complementary relationship between formal education, education for employment and physical capital.